High performance transparent conductors for touch devices - Lee, Ryan Ming Yao (2019)
With an increasing demand to process more information through a smaller device, the semiconductor industry has been increasing transistor density. Transistor density in turn translates to a wider spectrum of applications and uses. These applications in optoelectronics can be complemented with high performing transparent conductors playing a key role. Transparent conductors can be made by using a variety of materials. Currently, the most common material used is Indium Tin Oxide (ITO). There are many advantages in using ITO but with flexible optoelectronics emerging in the market, there needs to be a suitable replacement for the brittle predecessor. One key area that has been amassing a lot of attention is the advancement and utilization of nanometal wires. Nanometal wires include Gold, Silver and Copper nanowires. All of which have excellent conductivity. Among the three mentioned, Copper not only has excellent intrinsic conductivity but is also highly abundant and cheap. This peaks an interest to research copper nanowires to make it suitable as a replacement to ITO. Herein, this work provides a study of the growth process of copper nanowires. The material characterization necessary to support the data. Also, the integration of those copper nanowires grown in-house, in a variety of methods. There are numerous ways to grow copper nanowire and chemical method of growth is chosen here. The growth method is easy to scale-up in terms of manufacturing and seems to be beneficial to many areas in the long run. A modified method of vacuum transfer is also explored to improve the efficiency and result of integration.